Electrical conduction mechanism of rare-earth calcium oxyborate high temperature piezoelectric crystals. (15th January 2020) - Tian, Shiwei; Li, Lili; Lu, Xinyu; Yu, Fapeng; Li, Yanlu; Jiang, Chao; Duan, Xiulan; Wang, Zhengping; Zhang, Shujun; Zhao, Xian
Abstract: The electrical conduction behavior of piezoelectric crystals is critical in the design of piezoelectric sensors for use at elevated temperatures. The electrical resistivity and dielectric properties of rare-earth calcium oxyborate crystals ReCa4 O(BO3 )3 (ReCOB, Re = Y, Gd and Pr) are investigated in this report. The relationships between the electronic structures and electrical properties are then determined using X-ray photoelectron spectra and first principle calculations. Among the ReCOB type crystals, YCOB is found to possess the highest electrical resistivity and lowest dielectric loss. Nonlinearity of the electrical resistivity as a function of temperature for ReCOB crystals is then confirmed, corresponding to different conduction mechanisms. It is also revealed that the electrical conductivity of ReCOB type crystals is heavily influenced by oxygen vacancy defects at relatively lower temperatures (below ∼600 °C), while both vacancy defects and band gap contribute to conductivity at elevated temperatures (above ∼600 °C). Graphical abstract: The electrical conduction mechanism of ReCa4 O(BO3 )3 (Re: rare-earth elements and Y) type high-temperature piezoelectric crystals. Image, graphical abstract